Resistensi Perempuan Difabel dalam Hunchback Karya Ichikawa Saō: Perspektif Feminist Disability Studies - Yunita El Risman; Fithyani Anwar; A. Achmad Fudail (HUMANIKA, 2026)
This article examines forms of resistance enacted by a disabled woman protagonist in Ichikawa Saō’s novel Hunchback (2023). The novel portrays a female character with congenital myopathy who lives in close relation to medical technology and institutional care. Employing a qualitative interpretive approach through close reading, this study draws on Rosemarie Garland-Thomson’s feminist disability theory to analyze how the disabled body is represented and negotiated within structures of power.The findings reveal three major forms of resistance: (1) resistance against the desexualization of disabled bodies through the assertion of sexual desire and embodied experience; (2) resistance against the stigma of unproductivity through narrative production and authorship; and (3) resistance against the politics of staring through the strategic use of digital technology as a medium of subject formation.The study argues that disability in the novel is not merely portrayed as a biological condition, but as a socially constructed category that can be contested through narrative articulation. This research contributes to contemporary Japanese literary studies by centering disability as a primary analytical lens and by expanding discussions of women’s resistance within frameworks of ableism and normate femininity.